2015
DOI: 10.1016/j.eururo.2014.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Use of Perioperative Chemotherapy for Localized and Locally Advanced Muscle-invasive Bladder Cancer: A Sign of Changing Tides

Abstract: Background Despite the documented survival benefit conferred by neoadjuvant (NAC) and adjuvant chemotherapy (AC), there has been a slow adoption of guideline recommendations for the use of perioperative chemotherapy (POC) in patients with muscle-invasive bladder cancer (MIBC). Objective To evaluate temporal trends in POC utilization and identify factors influencing POC delivery in a representative cohort of patients with MIBC. Design, setting, and participants Retrospective cohort study identifying factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
117
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(133 citation statements)
references
References 22 publications
(32 reference statements)
9
117
0
4
Order By: Relevance
“…24 Regional differences within the province were evident, and in Calgary in 2011 the referral rate was still only 25.0% in spite of the development of provincial guidelines. Possible reasons for poor uptake in Calgary include skepticism on the part of some surgeons regarding the benefits of NACT, lack Neoadjuvant chemotherapy in muscle-invasive bladder cancer of a formal referral pathway to medical oncology for patients with MIBC being considered for cystectomy, and anecdotal evidence of an imbalance in surgeon volumes (i.e., more surgeons are performing cystectomies in Calgary than in Edmonton), leading to greater variability in practice.…”
Section: Discussionmentioning
confidence: 99%
“…24 Regional differences within the province were evident, and in Calgary in 2011 the referral rate was still only 25.0% in spite of the development of provincial guidelines. Possible reasons for poor uptake in Calgary include skepticism on the part of some surgeons regarding the benefits of NACT, lack Neoadjuvant chemotherapy in muscle-invasive bladder cancer of a formal referral pathway to medical oncology for patients with MIBC being considered for cystectomy, and anecdotal evidence of an imbalance in surgeon volumes (i.e., more surgeons are performing cystectomies in Calgary than in Edmonton), leading to greater variability in practice.…”
Section: Discussionmentioning
confidence: 99%
“…It has been over a decade 9,10 . Similarly, our study noted elderly age and increased comorbidity to be associated with decreased NAC utilization.…”
Section: Discussionmentioning
confidence: 99%
“…Although several observational studies identified a significant increase in the utilization of NAC up until 2010, contemporary national cancer registry data beyond this is lacking 4,9,10 . As such, in this study, we examine trend of the utilization of NAC and explore factors associated with its delivery.…”
Section: Introductionmentioning
confidence: 99%
“…8 Similarly, an Australian study showed an uptake of 17% increasing over time. 9 Nonetheless, in the context of Level 1 evidence, these rates are low, and these retrospective studies do not help us understand why.…”
mentioning
confidence: 99%